Potensi Ekstrak Etanol Daun Strobilanthes crispus Sebagai Antidiare - Arum Suproborini; Mochamad Soeprijadi Djoko Laksana; Lisniawati Lisniawati (EnviroScienteae, 2020)
Strobilanthes crispus plants are very potential as natural antidiarrheal drugs because of their phytochemical content, namely tannins, silicates, and catechins which are natural compounds of the flavonoid group. This study aimed to determine the potential of Strobilanthes crispus extract as an anti-diarrhea drug. The target of this study was to test the potential of ethanol extract of the leaves of Strobilanthes crispus as antidiarrheal. This study used the experimental laboratory method. The research stages included the selection of herbal ingredients, manufacturing of simplicia, ethanol extraction of Strobilanthes crispus using remaceration method, and testing the potential of ethanol extract of the leaves of Strobilanthes crispus against Escherichia coli and Streptococcus mutans using a good diffusion method with three replications each, measuring the diameter of the inhibition zone. The measurement results of inhibitory zone diameters of Strobilanthes crispus extract against Escherichia coli and Streptococcus mutans bacteria at concentrations of 15%, 30%, 45%, 60%, 75% each were 0 mm and at 100% concentration, the average was 16.33 mm for Escherichia coli and 17 mm for Streptococcus mutans. Based on the diameter of the inhibition zone showed MIC to Escherichia coli and Streptococcus mutans at a concentration of 100%. Strobilanthes crispus extract is more effective for diarrhea caused by Streptococcus mutans than Escherichia coli.